Economic Integration in MENA : The GCC, the Maghreb, and the Mashreq - Akhtar, Shamshad; Rouis, Mustapha (World Bank, Washington, DC, 2012)
Though the Middle East and North Africa (MENA) region has weathered the recent global financial and economic crisis relatively well, it still faces daunting medium-term challenges. These include high unemployment (especially among young people), vulnerability to oil and food price shocks and water scarcity and inefficiencies of public sectors. Integration of the region into the global economy has been slow. Of particular concern is the stagnation in the region's share of global non-oil exports, an indication of missed opportunities for diversification and growth. Integration within the region, while rising, is also on the low side when compared with other middle- and high-income regional blocs. To start off the removal of intraregional tariffs under the Pan-Arab Free Trade Area (PAFTA) and the adoption of low common tariffs by the Gulf Cooperation Council (GCC) which coupled with improvements in infrastructure, especially roads and telecommunications is generating benefits. But much remains to be done, especially in reducing nontariff barriers to trade, harmonizing policies and procedures, and facilitating cross-border trade through development of infrastructure links and trade facilitation. Fortunately, trade in services has recently emerged on the agenda of national and regional authorities; this is an area of substantial potential welfare gain for the region.